Rice husk as a pore-forming agent: impact of particle size on the porosity and diametral tensile strength of porous alumina ceramics - T. T., Dele-Afolabi; M. A., Azmah Hanim; D. W., Jung; R. A., Ilyas; R., Calin; A. R., Nurul Izzah (MDPI, 2022)
This study describes the porosity and particle size effects of rice husk pore former on the diametral tensile strength of porous alumina (Al2O3) ceramics. Porous Al2O3 ceramics with high porosity and sufficient diametral tensile strength were successfully prepared by the pore-forming agent method using rice husk (RH) as the pore former according to the sample formulation Al2O3-xRHy (where ‘x’ denotes the particle size range in µm and ‘y’ denotes the percent weight content (wt%) of RH). The thermogravimetric analysis (TGA) and X-ray diffractometer (XRD) results revealed that silica was retained as rice husk ash in the developed porous Al2O3 after the decomposition of the starting rice husk pore former. Microstructures of the as-prepared porous Al2O3 ceramics having different RH additions exhibited hierarchical pore structures with increased particle size of the pore-forming agent. Porosity increased with larger particle size range of rice husk where the Al2O3-63RH5 demonstrated the least porosity (44.2 vol%), while the highest porosity (70.9 vol%) was demonstrated by the Al2O3-125–250RH20. The diametral tensile strength of the RH-shaped porous alumina ceramics declined from 16.97 to 0.65 MPa with increased particle size of the rice husk.